Cardiac Disease Patterns in Northern Malawi: Epidemiologic Transition Perspective - Soliman, Elsayed Z. (J Epidemiol, 2008)
BACKGROUND: Cardiovascular disease (CVD) is a strongly emerging problem in developing countries. The documentation and prediction of CVD patterns are important for policy makers if actions are to be taken to curb this problem. We aimed to document the current CVD patterns in Malawi, and associate these patterns to the theory of epidemiologic transition as a means of predicting future CVD patterns. METHODS: We retrospectively analyzed the data recorded in the register of the cardiac clinic in Mzuzu Central Hospital-the only cardiac clinic run by a cardiologist in Malawi-from 2001 through 2005. The findings were interpreted in the context of the epidemiologic transition theory. RESULTS: Out of the 3908 new Malawian patients included in the 5-y period register, 34% had valvular heart disease (mainly rheumatic heart disease (RHD)); 24%, hypertensive heart disease; 19%, cardiomyopathies; and 14%, pericardial diseases. The other CVD patterns included congenital heart disease and arrhythmias, each representing 4% of the registered patients. Among the 1% comprising other CVD patterns, 3 cases were documented to have coronary heart disease, all of which happened in 2005. CONCLUSION: Malawi is in the stage of receding pandemics, which is characterized by CVD patterns predominated by RHD, cardiomyopathies, and hypertensive heart disease. However, continuous observation is required to detect signs of emerging “degenerative-related” CVD patterns, which is another stage in the epidemiologic transition.